2021
DOI: 10.3389/fimmu.2021.632383
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Sirtuin-1 in Immune Response and Systemic Lupus Erythematosus

Abstract: Systemic lupus erythematosus (SLE) is a potentially fatal multisystem inflammatory chronic disorder, the etiology and pathogenesis of which remain unclear. The loss of immune tolerance in SLE patients contributes to the production of autoantibodies that attack multiple organs and tissues, such as the skin, joints, and kidneys. Immune cells play important roles in the occurrence and progression of SLE through amplified immune responses. Sirtuin-1 (SIRT1), an NAD+-dependent histone deacetylase, has been shown to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 117 publications
(107 reference statements)
0
14
0
Order By: Relevance
“…SIRT1 can inhibit NF-κB pathway directly by itself or indirectly via forkhead family of transcription factors (FoxO) 16,18 . SIRT1 deacetylase was initially shown to deacetylate RelA/p65 at lysine 310 residue, which leads to reduced NF-κB transcriptional activity [19][20][21] . Substrates of SIRT1 are particularly abundant and include NF-κB RelA/p65, AP-1 family transcription factor c-Jun, and c-Myc.…”
Section: Discussionmentioning
confidence: 99%
“…SIRT1 can inhibit NF-κB pathway directly by itself or indirectly via forkhead family of transcription factors (FoxO) 16,18 . SIRT1 deacetylase was initially shown to deacetylate RelA/p65 at lysine 310 residue, which leads to reduced NF-κB transcriptional activity [19][20][21] . Substrates of SIRT1 are particularly abundant and include NF-κB RelA/p65, AP-1 family transcription factor c-Jun, and c-Myc.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies on Sirt1 have indicated that decreased Sirt1 expression or activity contributes to the enhancement of T cell activation, thereby leading to the occurrence of autoimmune diseases 58 . The immunoregulatory function of Sirt1 is dependent on the cell types and specific substrates that are targeted within the immune response.…”
Section: Sirt1mentioning
confidence: 99%
“…SLE, an incurable autoimmune disease, is due to inappropriate immune responses to nucleic acids containing cellular particles from the innate and adaptive immune system ( Qiu et al, 2021 ). The deposition of autoantibodies in kidney, skin, and lung is a characteristic of SLE ( Bialas et al, 2017 ).…”
Section: The Function Role Of Il-38 In Autoimmune Diseasesmentioning
confidence: 99%